2009
DOI: 10.1111/j.1746-1561.2009.00411.x
|View full text |Cite
|
Sign up to set email alerts
|

Correlates of Depressive Symptoms in Urban Youth at Risk for Type 2 Diabetes Mellitus

Abstract: Because depressive symptoms may affect ability to engage in healthy behavior changes, evaluation and treatment of depressive symptoms should be considered in preventive interventions for youth at risk for T2DM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
24
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(27 citation statements)
references
References 32 publications
2
24
0
Order By: Relevance
“…3,7,9,29,45,46 Jaser and colleagues 45 showed that youth with higher levels of depressive symptoms had higher BMI, and depressive symptoms also showed a strong inverse correlation with self-efficacy. The National Longitudinal Study of Adolescent Health (Add Health) showed that depressed adolescents were twice as likely to become obese than adolescents without depression.…”
Section: Discussionmentioning
confidence: 99%
“…3,7,9,29,45,46 Jaser and colleagues 45 showed that youth with higher levels of depressive symptoms had higher BMI, and depressive symptoms also showed a strong inverse correlation with self-efficacy. The National Longitudinal Study of Adolescent Health (Add Health) showed that depressed adolescents were twice as likely to become obese than adolescents without depression.…”
Section: Discussionmentioning
confidence: 99%
“…380 A large study of adolescents at risk for T2DM by virtue of high BMI together with a family history of diabetes mellitus found that depressive symptom severity was directly associated with BMI and fasting insulin levels. 381 However, other studies have not found associations between emotional/behavioral problems and metabolic control. 382 Screening for depression is advised for adolescents overall, 383 and this may be especially important for those with diabetes mellitus.…”
Section: Depressionmentioning
confidence: 94%
“…Sedentary lifestyle and unhealthy dietary behaviors are 2 important contributors to childhood and adolescent obesity. Obese children and adolescents have a higher prevalence of childhood asthma, 1 sleep apnea, 2 type‐2 diabetes, 3 renal injury, 4 emotional problems, 5‐7 and adulthood overweight 8 and other comorbidities 9 . Previous data indicated that body mass index (BMI) and percentage body fat were negatively related to self‐reported academic performance (ie, school grades) among children 11 to 14 years old 10 and that low aerobic fitness and obesity were associated with low standardized test scores in fifth to ninth graders 11 .…”
mentioning
confidence: 99%